Identifikasi Berpikir Kreatif Mahasiswa Melalui Metode Mind Mapping - FATMAWATI, BAIQ (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
The learning closely associated with the use of the brain as the centred of mental activity begin from the understanding, processing, until inference information. To optimize learning outcomes, the learning process using whole-brain approach. Creative thinking is a mental activity to create relationships continuous that were found the right combination includes aspects of cognitive, affective, and metacognitive. Thepurposesof this research to reveal of students creative thinking skills in the material the fermentation through mind mapping. This research is descriptive statistics which describe the student’s creative thinking skills that have, without giving specific mind map treatment. The subject is students of biology education semesters V. The results of analysis data showed that the scores of creative thinking skills students are: Fluency(Score 3; 21, 73%.Score 2; 39, 13%. Score 1; 39,13%). Flexibility(Score 3; 21, 73%.Score 2; 30, 43%. Score 1; 47, 82%) dan Originality(Score 3; 0%. Score 2; 0%. Score 1; 17.39%.Based on data, it can be concluded that the students have not be able to bring their creative ideas through mind mapping